A new species of Pleurothallis (Orchidaceae: Pleurothallidinae) from Zamora in the Province of Zamora Chinchipe, Ecuador - Jiménez, Marco M.; Horna, Luis Ocupa; Vélez-Abarca, Leisberth (Phytotaxa, 2021)
N/A